2010
DOI: 10.3109/13697130903568518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a health education program on climacteric women

Abstract: The health education program changed the cognitive actions of climacteric women, which resulted in continuously improved menopausal symptoms, quality of life and autonomic nervous system activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
1
8
0
3
Order By: Relevance
“…The adjustment of the autonomic nervous system (ANS) involves the balance of sympathetic and parasympathetic nerve activity and can represent changes in psychological status 6) . Numerous studies have indicated that HRV and the adjustment of ANS can be used to assess the psychological status of humans, such as depression and anxiety 6,7) . We hypothesized psychological status and heart function of post-menopausal women could be assessed via HRV and the adjustment of ANS.…”
Section: Introductionmentioning
confidence: 99%
“…The adjustment of the autonomic nervous system (ANS) involves the balance of sympathetic and parasympathetic nerve activity and can represent changes in psychological status 6) . Numerous studies have indicated that HRV and the adjustment of ANS can be used to assess the psychological status of humans, such as depression and anxiety 6,7) . We hypothesized psychological status and heart function of post-menopausal women could be assessed via HRV and the adjustment of ANS.…”
Section: Introductionmentioning
confidence: 99%
“…Berbagai gejala dan ketidaknyamanan akan muncul pada masa menopause. Delapan puluh persen perempuan melaporkan bahwa adanya ketidaknyamanan yang terjadi saat klimakterium seperti sakit kepala, masalah seksual, takikardi, hot flushes, berkeringat dan insomnia yang secara signifikan dapat menurunkan kualitas hidup (Senba & Matsuo, 2010). Kurangnya pengetahuan dan akses informasi merupakan tantangan besar yang dihadapi oleh wanita menghadapi menopause (Khademi, 2003).…”
Section: Pendahuluanunclassified
“…Berdasarkan penelitian yang telah dilakukan oleh Senba & Matsuo (2010) didapatkan hasil bahwa 22,7% perempuan klimakterik tanpa gejala, 36,4% mengalami gejala yang sedang sehingga diperlukan modifikasi perilaku dan gaya hidup, dan 36,4% mengalami gejala yang berat. Selain gejala klimakterik, dalam penelitian ini juga didapatkan hasil bahwa 30% wanita klimakterik mengalami gangguan fisik, 10% mengalami gangguan psikologis dan 15% mengalami stres.…”
Section: Pendahuluanunclassified
“…This includes gradual physiological degeneration, with a considerable decrease in the production of sleep quality-regulating hormones such as estrogen and progesterone. In addition, because women have different social and cultural expectations than men (Senba & Matsuo, 2010), the multi-faceted phenomenon produces changes in the sleep-controlling neuroendocrine system, causing sleep disorders (Manocha, Semmar, & Black, 2007). Studies done on the prevalence of menopausal symptoms have reported that approximately 20 to 60% of menopausal women complain about having sleep disorders (Eichling & Sahni, 2005;Moilanen et al, 2010;Woods & Mitchell, 2005), indicating the prevalence and severity of sleep-related problems.…”
Section: Introductionmentioning
confidence: 97%
“…It is generally believed that the combined use of multiple behavioral techniques to improve sleep quality is more effective than a single technique. However, current solutions introduced in most studies employ only a single intervention to improve the sleep disturbance experienced by menopausal women (Elavsky & McAuley, 2007;Senba & Matsuo, 2010). Studies that have implemented two or more intervention strategies are scant.…”
Section: Introductionmentioning
confidence: 98%